Physician Beliefs about the Meaningful Use of the Electronic Health Record: A Follow-Up Study - Emani, Srinivas; Ting, David Y.; Healey, Michael; Lipsitz, Stuart R.; Karson, Andrew S.; Bates, David W. (Applied Clinical Informatics, 2017)
Background There is continuing interest in how physicians are responding to the meaningful use of the electronic health record (EHR) incentive program. However, little research has been done on physician beliefs about the meaningful use of the EHR.Objective This study aims to conduct a follow-up study of physician beliefs about the meaningful use of the EHR.Methods Online survey of physicians at two academic medical centers (AMCs) in the northeast who were participating in the meaningful use of the EHR incentive program and were using an internally developed EHR was conducted.Results Of the 2,033 physicians surveyed, 1,075 completed the survey for an overall response rate of 52.9%. Only one-fifth (20.5%) of the physicians agreed or strongly agreed that meaningful use of the EHR would help them improve quality of care, and only a quarter (25.2%) agreed or strongly agreed that the meaningful use of the EHR would improve the care that their organization delivers. Physician satisfaction with the outpatient EHR was the strongest predictor of self-efficacy with achieving stage 2 of the meaningful use of the EHR incentive program (odds ratio: 2.10, 95% confidence interval: 1.61, 2.75, p < 0.001). Physicians reported more negative beliefs in stage 2 than stage 1 across all belief items. For example, 28.1% agreed or strongly agreed that the meaningful use of the EHR would decrease medical errors in stage 2 as compared with 35.9% in stage 1 (p < 0.001).Conclusion Only one-fifth of the physicians in our study believed that the meaningful use of the EHR would improve quality of care, patient-centeredness of care, or the care they personally provide. Primary care physicians expressed more negative beliefs about the meaningful use of the EHR in stage 2 than in stage 1. These findings show that physicians continue to express negative beliefs about the meaningful use of the EHR. These ongoing negative beliefs are concerning for both implementation and policy.
Keywords: electronic health records; physicians; beliefs; meaningful use; self-efficacy